The study of individual technical and tactical actions of young players 10–11 years with the game role - Лебедєв [Lebedev S.] Сергій Ігорович (Slobozhanskyi Herald of Science and Sport, 2012)
In this work discusses the performance of technical and tactical actions of young players during games. The quantitative and qualitative characteristics of the players play different roles. Found that the line of defense, players significantly inferior in the technical and tactical techniques as to intercept the ball and shots on target players to other lines. Players line dominated the midfield ball tricks, passing the ball back and forth, interceptions. Players line of attack – strikes on target.